The relationship op poetry and prose in Old Serbian literature - Kostić Tmušić, Aleksandra S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This work is pointing out relations between poetry and prose in contemporary understanding of this problem, on one hand, and the comprehension of these relations in Serbian medieval literarary works, on the other hand. Literature, which was created in contemporary, modern period, is making clear difference in relations between poetry and prose, while in studies of Old Serbian literature there are tendencies for deleting lines between prosaic and poetic way of speaking, therefore even rhythmical poems are sometimes called prose. Only conditionally, some genres can be classified as prosaic, other as poetic, while a big group remains mixed, because, for some features it may be considered as poetic, and for some features it may be considered as prosaic. As well as in all cultural areas, Byzantine orientation had decisive influence on forming and developing of Serbian medieval literature. Byzantine literary tradition has become paradigm for establishing and determining of philosophy, aesthetics and poetic in period of the earliest Serbian literature, which had as a crucial mission to overmaster early Christian literary heritage, which was, basically, Byzantine, as well as to overmaster the other medieval literatures. Very important things for poetry in Old Serbian literature are its rhythm, melody and sound. These terms are wider than term linguistic values. Elements which are creating rhythm, melody and sound are elements of the language. However, they do not stand only as sounds but, also, have certain linguistic values. Aim of this work is to get closer apprehension of Old Serbian literature throughout intellection of old Serbian writer and poet, guiding by laws of medieval poetics and aesthetics, but seen through contemporary scholars of literature eyes.